Intraoperative Deliberate Hypotension: Comparison of Dexmedetomidine Infusion Alone and in Combination with Iignocaine - Mamoona Shaikh, Kauser Shaikh, Fayaz Ahmed Memon, Muhammad Tahir, Jamil Ahmed Khanzada, Javeria Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To explore the effects of dexmedetomidine infusion combined with lignocaine on the intraoperative hemodynamic profile. Study Design: randomized, double-blind study Place and Duration of Study: Department of Anesthesia, Isra University Hospital, Hyderabad from 1st May 2021 to 31st October 2021. Methodology: Sixty patients from the daily operation list were randomly assigned to group D (dexmedetomidine intravenous infusion only) and group LD (dexmedetomidine plus lignocaine intravenous infusion) using a sealed envelope system. Results: The majority of the patients presented ASA status II (41.7%) were in the age group of 35-44 years (23.3%) and had BMI ranging from 25-34. Analysis of various clinical parameters showed a significant difference between group D and LD in terms of reduced heart rate, average mean arterial pressure, and need for transfusion. A higher number of patients receiving combination infusion had negligible blood loss with reference to patients maintained at dexmedetomidine alone. The satisfaction levels of the surgeon and attending anesthetist were significantly higher for surgical outcomes in the group receiving a combinative infusion of dexmedetomidine and lignocaine. Conclusion: The hemodynamic profiles of patients undergoing different surgeries showed significant favor for the combination of dexmedetomidine and lignocaine infusion as compared to infusion of dexmedetomidine only.